Cultural Public Sphere: Tracking the Yogyakarta City Policy Agenda through the #JogjaOraDidol Hashtag on Twitter - Ujang Fahmi (Indonesian Association for Public Administration, 2019)
Instead of studying the virtual space using the Political Public Sphere concept, this study adopts the Literary Public Sphere point of view to examine and narrate the nature of a Cultural Public Sphere in social media. The researchers see interactivity in social media as an articulation of expression involving emotions and aesthetics (affective communication). Using the mixed method of Topic Modelling, Social Network Analysis (SNA), and Discourse Analysis in the case of the presence of the #JogjaOraDidol hashtag in Twitter, this study conclude that the Cultural Public Sphere has three dimensions of Public Sphere as introduced by Dahlgren (2005). The dynamic of inclusivity for anyone to express themselves and to engage in public issues discussions indicates that space is inclusive not only because of the technical support of the media but also because of the commitment of its users (structural dimension). The emergence of three virtual communities (fans, artists and activists) that develop a collective identity represents a subset of the real local population and demonstrates the ideal role taking of the representational aspect of Public Sphere. The interactional one is indicated by the discourse constructed using reflexive but straightforward symbols represent the interaction between users and the meaning that users do to the contents of the media used. Meanwhile, the real action show of the discourse develops virtually does not entrap the user in pseudo-empowerment. As an implication, using specific parameter, notably the hashtag identifies a social movement, policymakers can use data from social media in the agenda-setting process. Additionally, in the context of #JogjaOraDidol, soft data can also be used to evaluate the moratorium policy of granting the hotel's construction permit.